(untitled) (Лучшие интеллектуальные исследования, 2025)
This article analyzes the physical and mechanical nature of geothermal energy, its sources, and the technologies used to harness it. Geothermal energy exists in the form of heat stored in the deep layers of the Earth’s crust and is released through natural steam, hot water, or heated rocks. This energy source is characterized by its renewable nature and environmental safety. The paper examines the various applications of geothermal energy, including electricity generation, heating systems, and greenhouse agriculture. In addition, the global development of geothermal energy, advanced technologies, and the experiences of leading countries such as Iceland, Italy, the United States, and the Philippines are discussed.